Knowledge before action Islamic learning and Sufi practice in the life of Sayyid Jalāl al-Dī n Bukhārī Makhdūm-i Jahāniyān - Steinfels, Amina M. (Columbia University of South Carolina Press, 2012)
The education of a Sufi shaykh. Initiation into the Sufi path -- Pilgrimage and travel -- Teaching and practice. Book-learning and Islamic law -- Ritual and practice -- Money, non-Muslims, women, and saints -- Served by the inhabitants of the world. A public figure -- Legacy
Includes bibliographical references and index. - Description based on print version record
Online-Ausg.
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Maḵẖdūm Jahāniyān Jahāṉ Gasht, Jalāluddīn -1383; Mak̲h̲dūm Jahāniyān Jahān̲ Gasht, Jalāluddīn -- -1383; Makhdum Jahaniyan Jahan Gasht, Jalaluddin d. 1383; Mak̲h̲dūm Jahāniyān Jahān̲ Gasht, Jalāluddīn; Sufis -- Biography; Muslim scholars -- Biography; Sufism -- History; Sufis -- Biography; Sufism -- History; Muslim scholars -- Biography; RELIGION ; Islam ; Sufi; Muslim scholars; Sufis; Sufism; Sufismus; Biographies; History; Südasien; Electronic books -- Electronic books